PRESERVASI SEBAGAI UPAYA UNTUK MENJAGA KELESTARIAN DAN MEMPERPANJANG USIA ARSIP STATIS KONVENSIONAL - Purnomo Purnomo (Jurnal Pustaka Ilmiah, 2018)
Observation or preservation of archives is a process and effort in protecting the physical archive against damage or destructive elements and restoration / resvarasi damaged part of the archive, which is caused by factors from the (intrinsic) archive itself as well as factors from the outside (extrinsic) physical archive itself. The importance of preservation of archives in each institution is for the institution’s long-term interests. Because the archive preservation program will be able to avoid more severe damage, loss of material and information. The purpose of preservation in the archive itself is to maintain its sustainability and extend the age of its use. So that it can survive and be more broadly useful, For this reason there is an effort to divert the provision of archives such as efforts to digitize archives so that they remain stored in electronic form to save space and maintain them, because many archival conditions are not feasible but have very important values.